Fractional Order PD Control of Friction-Induced Vibrations in a Continuous System - Kokane, Tejas; Saha, Ashesh (Journal of Applied Nonlinear Dynamics, 2026)
Fractional-order PD (PD^λ ) control of friction-induced vibrations in a beam-mass model is analysed in this paper. Mathematical modelling of the system with a piezo-patch actuator bonded to the beam surface is presented. Linear stability analysis is performed to determine the stability boundary corresponding to the Hopf bifurcation points. The nature of bifurcation is found to be supercritical from the non-linear analysis by the method of averaging. The role of fractional-order on the effectiveness of the controller in quenching friction-induced vibrations is thoroughly investigated. The efficacy of the controller with varying size and locations of the piezo-patch is also studied.